Performance of sewage sludge reuse in the manufacturing of fired bricks - K. Moulato; M. Ammari; L. Ben Allal (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The disposal of sludge from wastewater treatment plants into the natural environment represents a major danger to the environment and human health. The use of urban sludge as raw material in the manufacture of clay bricks not only reduces the amount of sludge but also transforms it into useful materials. This paper studies the physicochemical, geotechnical, mineralogical, mechanical, and environmental characterizations of earth bricks with the objective of evaluating the performance of the sewage sludge and eventually studying its consistency with natural clay to produce brick samples. The aim of the study is to evaluate the properties of bricks made from sewage sludge, innovating an effective elimination of the urban sludge.METHODS: Measurements of sludge heavy metal concentrations are made with an inductively coupled plasma on a 63-micrometer fine particle fraction. Organic matter performed by the Walkley-Black assay and the loss on ignition method for comparison. Volatile matter, total nitrogen, moisture content, dryness, pH, methylene blue assay, and carbonate rate were determined using a 2-millimeter Bernard calcimeter by volumetric method. Density, plasticity, liquidity index, and pore distribution were determined using a mercury porosimeter, and the specific surface and granulometric analysis have been established. Mineralogical characterization of sludge by X-ray diffraction, and X-ray fluorescence has been provided for comparative analysis with natural clay. The brick samples were then shaped, dried, fired at 930 Celsius degree, and qualified by tests, including linear and mass shrinkage, porosity, water absorption, density, compressive strength, X-ray diffraction, and leaching.FINDINGS: The analyses by X-ray fluorescence and X-ray diffraction of the sludge revealed the presence of mineral constituents, including calcite, silica, kaolinite, and dolomite and shows an important amount of silicon dioxide (31.6 percent) and aluminum oxide (11.5 percent). The sludge was classified as fine with a silty-clay character, with a plasticity index of 54.63 percent, and was therefore very plastic, and had trace element concentrations below the authorized standards. A sample containing 10 percent of sludge gives a strength of 25.9 megapascal which is close to that of the control brick. The bulk density analysis of brick sample 1 was 1.57 grams per cubic centimeter and classifies it as a light building material. Above 20 percent of samples substitution, their strength becomes less reliable, due to the large amount of organic matter that burns during firing which creates pores in the finished product.CONCLUSION: These results suggest that thermal processes limit the leaching of metals and are practically inaccessible to the ecosystem, so the brick cannot harm the environment. As the sludge content increases, the final structure no longer conforms to the control sample. This incorporation of natural clay and sludge allows to obtain a lighter brick than the conventional one. The study suggests that a 10 percent incorporation of sludge allows the production of efficient bricks and reinforces the potential of this valorization technique, which efficiently contributes to the accomplishment of sustainable waste management objectives. By helping reduce waste produced in very large quantities, this study contributes to the protection of the environment and human health.